2003
DOI: 10.1093/jn/133.5.1448s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper, Zinc, Selenium and Tellurium in the Cellular Defense against Oxidative and Nitrosative Stress

Abstract: The trace elements copper, zinc and selenium are linked together in cytosolic defense against reactive oxygen and nitrogen species. Copper, zinc-superoxide dismutase catalyzes the dismutation of superoxide to oxygen and hydrogen peroxide. The latter and other hydroperoxides are subsequently reduced by the selenoenzyme glutathione peroxidase (GPx). Cytosolic GPx can also act as a peroxynitrite reductase. The antioxidative functions of these trace elements are not confined to being constituents of enzymes: 1) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
165
2
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(176 citation statements)
references
References 45 publications
0
165
2
9
Order By: Relevance
“…These GPx play a significant role in protecting cells against oxidative damage from ROS and RNS, which include superoxide, hydrogen peroxide, hydroxyl radicals, nitric oxide and peroxynitrite. [86][87] The other essential antioxidant selenoenzymes are the TrxR where they use thioredoxin (Trx) as a substrate to maintain a Trx/TrxR system in a reduced state for removal of harmful hydrogen peroxide. [88][89] There are three types of TrxR that have been identified, and these include cytosolic TrxR1, mitochondrial TrxR2 and spermatozoa-specific TrxR, (SpTrxR).…”
Section: -83mentioning
confidence: 99%
“…These GPx play a significant role in protecting cells against oxidative damage from ROS and RNS, which include superoxide, hydrogen peroxide, hydroxyl radicals, nitric oxide and peroxynitrite. [86][87] The other essential antioxidant selenoenzymes are the TrxR where they use thioredoxin (Trx) as a substrate to maintain a Trx/TrxR system in a reduced state for removal of harmful hydrogen peroxide. [88][89] There are three types of TrxR that have been identified, and these include cytosolic TrxR1, mitochondrial TrxR2 and spermatozoa-specific TrxR, (SpTrxR).…”
Section: -83mentioning
confidence: 99%
“…Such as potassium plays a main role in carbohydrate and protein metabolism. To keep the normal intracellular osmotic pressure; maintain the normal function of the nerve muscle and myocardial function and maintain cells inside and outside the acid-base balance, etc [15]. Ca was not only the main component of bones and teeth, also participate in a variety of physiological activities in the body.…”
Section: Discussionmentioning
confidence: 99%
“…P is related to the physiological function of Ca and Mg. The epidemiological studies showed that trace elements Fe, Zn and Cu were related to the incidence of coronary artery disease, and the mechanism is related to vascular cell dysfunction and inflammatory reaction [13,14,15]. It was reported that the deficiency of Mg causes the inhibition of glucose tolerance, carbohydrate and lipid metabolism, and degradation of serum high density lipoprotein [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…O zinco forma parte da enzima antioxidante citosólica, Cobre-Zinco Superóxido Dismutase (CuZn-SOD) 8,26 . Moléculas de superóxido são convertidas a peróxido de hidrogênio pela CuZn-SOD, a qual ativa as vias inflamatórias 8,27 .…”
Section: Interleucina-6unclassified